STRUCTURING OF THE KNOWLEDGE BASE STRUCTURING KNOWLEDGE BASE IN THE ENVIRONMENT AVIATION EXPLOITED OF A DECISION SUPPORT SYSTEM - Чоха, Ю. М. (Science-based technologies, 2013)
The necessity of applying a conceptual approach to methods of forming a knowledge base that provides the automated diagnosis and decision support system for the staff in the regular operation of a typical complex dynamic aviation object.